2018
DOI: 10.1038/s41598-018-21752-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile associated with distinct behavioral coping strategies of 129Sv and Bl6 mice in repeated motility test

Abstract: We investigated the metabolic outcome of different coping strategies in 129S6/SvEvTac (129Sv) and C57BL/6Ntac (Bl6) strains. Two different batches of male 129Sv and Bl6 mice were used. One batch was not subjected to any behavioral manipulations (home cage control; HCC), whereas the other batch was treated with saline for 11 days and exposed after every treatment to the motor activity measurement (repeated motility tested; RMT). Bl6 RMT mice displayed a robust increase in number of rearings during repeated test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 41 publications
(49 reference statements)
3
19
0
Order By: Relevance
“…However, this has been disproven and without foundation [7]. While numerous papers examined the metabolic profiles of inbred mouse strain 129 [8][9][10], little attention has been paid to the impact of sex on the development of metabolic syndrome caused by HFD.…”
Section: Introductionmentioning
confidence: 99%
“…However, this has been disproven and without foundation [7]. While numerous papers examined the metabolic profiles of inbred mouse strain 129 [8][9][10], little attention has been paid to the impact of sex on the development of metabolic syndrome caused by HFD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on above described data of DBA/2 mice we expect that 129Sv mice display stronger sensitization toward AMPH-induced hyper-locomotion compared to Bl6 strain. Previously, we have found the significant differences in the blood metabolite levels in Bl6 and 129Sv mice (Narvik et al, 2018 ). Thus, we expected to see significant differences in metabolite levels between these two mouse strains in response to repeated AMPH as well, especially in the levels of hexoses and lipid metabolites that are necessary to fuel the strong locomotor response.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, a preliminary analysis was performed to evaluate the impact of repeated saline administration on metabolic markers. The results indicated that altogether 52 metabolites were significantly different between 129Sv and Bl6 (Narvik et al, 2018 ). The values of 33 items were higher in Bl6 and 19 items were respectively elevated in 129Sv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations